Dental Age Estimation: Pattern Recognition of Root Canal Widths of Mandibular Molars. A Novel Mandibular Maturity Marker at the 18‐Year Threshold1. Issue 2 (1st December 2016) - Roberts, Graham J.; Lucas, Victoria S.; Andiappan, Manoharan; McDonald, Fraser
Abstract: The final stage of third molar development is used to assign a subject to above the 18‐year threshold. Some subjects exhibiting this final stage are less than 18 years. Radiographs from 1000 females and 1000 males age 16.00–25.99 years were examined. Each half‐year age band comprised 50 females and 50 males. Three categories of root canal widths (RCW) of the LL6, LL7, and LL8 [FDI 36, 37, and 38] were defined. Reproducibility was achieved by re‐assessing the same subjects 12 months apart. For females, the minimum value for RCW‐A was 16.33 years, RCW‐B 17.23 years, and RCW‐C 18.45 years. For males, the minimum values were RCW‐A 17.16 years, RCW‐B 18.29 years, and RCW‐C 18.16 years. The presence of RCW‐C in a female, and the presence of RCW‐B or RCW‐C in a male is compelling evidence that the subject is above the 18‐year threshold.